Role of Underwriters in A Company - Pattnaik, Annpurna; Talukdar, Rubi (International Journal of Psychosocial Rehabilitation, 2025)
One of the most familiar and visible element of the IPO process is the underwriter. The underwriter can be referred as the organization that is actually responsible for selling, organizing and pricing the issue. They are one of the most vital player in the financial market and hence there is need to regulate them and keep a watch on their functioning. In this paper we are going to understand the concept of what underwriters are and the SEBI guidelines to regulate the functioning of them. Along with its limitations and benefits of underwriters to the company and their role in IPO’s and financial market.